A PSICHOLOGICAL STUDY OF HIPNOSYS IN TRANSFORMATION OF RELIGIOUS BEHAVIOUR TOWARD TEENAGER IN ACEH TAMIANG - Afrida, Nina; Mahriza, Rita; Rahmah, Meutia; Santi, Nani Endri (State Islamic University of North Sumatra Indonesia, 2020)
Teenager or Aqil Baligh in Islam can be called transition phase from childhood into adulthood. In this age, a child is in critical period in which is tending to do a deviant behaviour such as in their religious. No exception, this case also occured in one of regent in Aceh. Unfortunately, It has not been a focus for those who are responsible for this. The alternative is offered can become one of solution; by stimulating them using hypnosis. For those, the research aims to find out whether hypnosis can increase significantly in teenagers’ religious behaviour in 11 to 18 years old. Single subject by multiple baseline design applied in this study, and two teenagers were as a sample. The result shows that the graph increases signifinatly in Akhlak (morals) but it did not work in Shalat and aurat, it was applied in both of samples. In conclusion, a hypnosis can be an alternative to solve a transformation of religious behaviour in Akhlak.